Attitudes of Icelandic school-children towards bullying and interventions - Sigurgeirsdóttir, Vanda; Arnarsson, Ársæll Már (Menntavísindasvið Háskóla Íslands, 2019)
Bullying is a serious and prevalent problem in schools in Iceland as in the rest of the world. Despite various actions taken by authorities to counter bullying, the results have not been as hoped for. In the latest wave of the Health behaviour in school-aged children in Iceland in 2018, 6.3% of students in 6th, 8th and 10th grade reported that they had been bullied 2-3 times a month or more often. In the current study we looked at the experience and attitudes of Icelandic school-children regarding several relevant factors, such as teacher intervention, student responsibilities, audience response, anti-bullying programs at school and fear of bullying. The aim of the study was to examine attitudes of elementary school students toward bullying and its interventions. Responses were collected from 10,651 students in 6th, 8th, and 10th grade in Iceland during the 2013-14 school year which equals 84% of the whole population for these age-groups. The questions on bullying were preceded by the following definition: “Here are some questions about bullying. We say a person is being bullied when another person or a group of people, repeatedly say or do unwanted nasty and unpleasant things to him or her. It is also bullying when a person is teased in a way he or she does not like or when he or she is left out of things on purpose. The person that bullies has more power than the person being bullied and wants to cause harm to him or her. It is not bullying when two people of about the same strength or power argue or fight”. The came two questions – one on bullying: “How often have you taken part in bullying another person(s) in school in the past couple of months?”; the other on victimization: “How often have you been bullied in school in the past couple of months?” There were five possible answers to both questions: 1) Never, 2) It has happened once or twice, 3) 2 or 3 times a month, 4) About once a week, and 5) Several times a week. For the purpose of this study only 2 or 3 times a month or more was considered as ...